Effectiveness of Distant/Remote Blessing Treatment on Cognitive-motor Function: A Randomized Double-blind Placebo-controlled Trial - Alice Branton; Mahendra Kumar Trivedi; Dahryn Trivedi; Sambhu Mondal; Snehasis Jana (Health Psychology Research)
# Background